Activation of KCNQ Channels Suppresses Spontaneous Activity in Dorsal Root Ganglion Neurons and Reduces Chronic Pain after Spinal Cord Injury - Wu, Zizhen (J Neurotrauma, 2017)
A majority of people who have sustained spinal cord injury (SCI) experience chronic pain after injury, and this pain is highly resistant to available treatments. Contusive SCI in rats at T10 results in hyperexcitability of primary sensory neurons, which contributes to chronic pain. KCNQ channels are widely expressed in nociceptive dorsal root ganglion (DRG) neurons, are important for controlling their excitability, and their activation has proven effective in reducing pain in peripheral nerve injury and inflammation models. The possibility that activators of KCNQ channels could be useful for treating SCI-induced chronic pain is strongly supported by the following findings. First, SCI, unlike peripheral nerve injury, failed to decrease the functional or biochemical expression of KCNQ channels in DRG as revealed by electrophysiology, real-time quantitative polymerase chain reaction, and Western blot; therefore, these channels remain available for pharmacological targeting of SCI pain. Second, treatment with retigabine, a specific KCNQ channel opener, profoundly decreased spontaneous activity in primary sensory neurons of SCI animals both in vitro and in vivo without changing the peripheral mechanical threshold. Third, retigabine reversed SCI-induced reflex hypersensitivity, adding to our previous demonstration that retigabine supports the conditioning of place preference after SCI (an operant measure of spontaneous pain). In contrast to SCI animals, naïve animals showed no effects of retigabine on reflex sensitivity or conditioned place preference by pairing with retigabine, indicating that a dose that blocks chronic pain-related behavior has no effect on normal pain sensitivity or motivational state. These results encourage the further exploration of U.S. Food and Drug Administration–approved KCNQ activators for treating SCI pain, as well as efforts to develop a new generation of KCNQ activators that lack central side effects.